Stem cells in degenerative lumbar spine disease: a review and focus on utility in Low- and Middle-Income Countries - Muhammad Usman Khalid; Mohammad Hamza Bajwa; Akbar Jaleel Zubairi (Journal of the Pakistan Medical Association, 2023)
Stem cell therapy is a common adjunct in regenerative medicine and has recently seen greater adoption in spinal surgery. Arthrodesis is typically achieved with iliac-crest bone grafts with several adverse events, leading to the development of alternative biomaterials. One such biomaterial is stem cells, which may be equal in terms of effectiveness but with significantly fewer complications. Low- and Middle-Income Countries (LMICs) have seen slow adoption of stem cell therapy due to resource constraints but may benefit the most from these techniques. We conducted a comprehensive review of literature in the PUBMED, Scopus, and Cochrane Library databases on the use of stem cells and stem cell-based biomaterials in spinal surgery. Our review showed promising results, from a variety of methods including augmentation of existing scaffold with mesenchymal stem cells or concentrated bone marrow aspirate. Continued...